The Gig Economy and Automation: Implications for Human Resource Management in Pakistan - Bashir, Madiha; Noor-e-Zahra, Syeda; Qaisar, Zobia (Inverge Journal of Social Sciences, 2024)
In the face of ground-breaking advancements such as automation, artificial intelligence, and the gig economy, the realm of human resource management (HRM) is undergoing a profound transformation. As the nature of work evolves, HRM practices must adapt to ensure both organizational performance and employee well-being. A primary focus of the study is the increasing emphasis on workforce flexibility. The rise of remote work, flexible schedules, and contingent labour has necessitated a shift in HRM practices. This research explores how organizations can effectively manage a diverse workforce while maintaining productivity and employee satisfaction. Additionally, the study examines the impact of job changes, including automation-driven task shifts and the emergence of new roles. It investigates how HR professionals can assist employees in adapting to these changes and acquiring the necessary skills for the future of work. Ethical considerations are also a central theme of this research. With the rise of AI and automation, questions surrounding data privacy, algorithmic bias, and ethical decision-making in the workplace have become increasingly pressing. The study explores the ethical implications of these technologies and provides guidance for HR professionals on developing ethical policies and practices. This research study underscores the critical role of HRM in fostering a productive and supportive work environment. It highlights the need for HR professionals to be strategic partners with business leaders, aligning HR practices with overall organizational goals. By understanding the challenges and opportunities presented by these revolutionary developments, HR professionals can equip their organizations to navigate the complexities of the contemporary workplace and achieve long-term success. This research offers a valuable resource for HR professionals, business executives, and policymakers seeking to understand the changing landscape of HRM and develop effective strategies for managing their workforce in the face of technological advancements and evolving workforce dynamics. References Adams-Prassl, J. (2019). What if your boss was an algorithm? Economic incentives, legal challenges, and the rise of artificial intelligence at work. Comp. Lab. L. & Pol'y J., 41, 123. Ali, Z., & Niaz, A. (2024). Impact of Leadership Styles on the Employees’ Engagement in Private Healthcare Industry of UAE. Inverge Journal of Social Sciences, 3(1), 7-27. Alizai, S. H., Asif, M., & Rind, Z. K. (2021). Relevance of Motivational Theories and Firm Health. Management (IJM), 12(3), 1130-1137. Ali, Z. A., Zain, M., Pathan, M. S., & Mooney, P. (2024). Contributions of artificial intelligence for circular economy transition leading toward sustainability: an explorative study in agriculture and food industries of Pakistan. Environment, Development and Sustainability, 26(8), 19131-19175. Asif, D. M. (2024). THE COMPLEXITIES OF BIOTERRORISM: CHALLENGES AND CONSIDERATIONS. International Journal of Contemporary Issues in Social Sciences, 3(3), 2175-2184. Asif, M. (2022). Integration of Information Technology in Financial Services and its Adoption by the Financial Sector in Pakistan. Inverge Journal of Social Sciences, 1(2), 23-35. Asif, M. (2021). Contingent Effect of Conflict Management towards Psychological Capital and Employees’ Engagement in Financial Sector of Islamabad. Preston University, Kohat, Islamabad Campus. Asif, M., Khan, A., & Pasha, M. A. (2019). Psychological capital of employees’ engagement: moderating impact of conflict management in the financial sector of Pakistan. Global Social Sciences Review, IV, 160-172. Asif, M., Pasha, M. A., Mumtaz, A., & Sabir, B. (2023). Causes of youth unemployment in Pakistan. Inverge Journal of Social Sciences, 2(1), 41-50. Asif, M., Pasha, M. A., Shafiq, S., & Craine, I. (2022). Economic impacts of post COVID-19. Inverge Journal of Social Sciences, 1(1), 56-65. Asif, M., & Sandhu, M. S. (2023). Social Media Marketing Revolution in Pakistan: A Study of its Adoption and Impact on Business Performance. Journal of Business Insight and Innovation, 2(2), 67-77. Asif, M., & Shaheen, A. (2022). Creating a High-Performance Workplace by the determination of Importance of Job Satisfaction, Employee Engagement, and Leadership. Journal of Business Insight and Innovation, 1(2), 9-15. Asif, M., Pasha, M. A., Shafiq, S., & Craine, I. (2022). Economic impaAsif, 2023 #79cts of post COVID-19. Inverge Journal of Social Sciences, 1(1), 56-65. Asghar, R. J., Qayyum, A., Zaheer, A., Mughal, A., & Khalid, S. (2011). Implementation of HR Practices in University Teachers of Pakistan. Information Management and Business Review, 3(3), 148-157. Asghar, R. J., Shah, M. U. Z. A. M. M. E. L., & Khan, J. A. (2021). Big Five Personality Traits and Training Transfer: Does Organizational Politics Matters. International Review of Basic and Applied Sciences, 9(4), 457-469. Aurangzeb, M. A. (2021). Role of Leadership in Digital Transformation: A Case of Pakistani SMEs. Aurangzeb, A. (2021). M., & Amin, MK (2021). Resources management and SME's performance. Humanities & Social Sciences Reviews, 9(3), 679-689. Aurangzeb, M., Tunio, M., Rehman, Z., & Asif, M. (2021). Influence of administrative expertise on human resources practitioners on the job performance: Mediating role of achievement motivation. International Journal of Management, 12(4), 408-421. Azad, T. (2023). The Impact of Technology in the Classroom: An Insight into Students' and Teachers' Psychological Perspectives. Inverge Journal of Social Sciences, 2(2), 66-83. Chintaradeja, P. (2022). Rhodes’ governance concept in relation to Thai public service. Inverge Journal of Social Sciences, 1(1), 1-12. Chompupor, P. (2023). The MICE labour market challenges in Thailand from experts’ perspective. Inverge Journal of Social Sciences, 2(2), 165–175. De Stefano, V. (2020). Algorithmic bosses and what to do about them: automation, artificial intelligence and labour protection. Economic and policy implications of artificial intelligence, 65-86. Darkwa, E., Inguva, H., Osafo-Adjei, C., & Acquah, B. (2024). The public sphere on a digital plane: The influence of the new digital media on Ghana’s democracy and the Public Sphere. Inverge Journal of Social Sciences, 3(2), 46-62. Inyang, U., G. Etuk, S., & Effiom, M. (2024). Employees’ Assessment of Impact of Information Systems on Operational Efficiency of Insurance Companies. Inverge Journal of Social Sciences, 3(3), 1–12. Iqbal, M. S., Rahim, Z. A., & Hussain, S. A. (2020). Industry 4.0 revolution and challenges in developing countries: a case study on Pakistan. Journal of Advanced Research in Business and Management Studies, 21(1), 40-52. Ishfaq, U., Imran, A., Joseph, V., Haqdad, U., & Asif, M. (2022). Mediating role of trust between emotional intelligence and project team performance in telecommunication sector. PalArch's Journal of Archaeology of Egypt/Egyptology, 19(4), 988-1005. Jamil, S. (2021). Artificial intelligence and journalistic practice: The crossroads of obstacles and opportunities for the Pakistani journalists. Journalism Practice, 15(10), 1400-1422. Khan, M. H. (2023). The role of recruitment and selection on organizational performance: An empirical investigation into the impact of recruitment and selection on organizational performance. Inverge Journal of Social Sciences, 2(2), 146-164. Khan, M. H. (2023). The influence of green HRM practices and green knowledge sharing on green service behaviors: Environmental Sustainability at Work: How Green HRM and Knowledge Transfer Influence Green Service Behaviors. Inverge Journal of Social Sciences, 2(2), 176-193. Khatun, R. (2023). Work from Home in Pandemic - An Indian Perspective. Inverge Journal of Social Sciences, 2(3), 77–95. Malik, A., Budhwar, P., & Srikanth, N. R. (2020). Gig economy, 4IR and artificial intelligence: Rethinking strategic HRM. In Human & technological resource management (HTRM): New insights into revolution 4.0 (pp. 75-88). Emerald Publishing Limited. Mangi, R. A., Jhatial, A. A., Shah, S. A. A., & Ghumro, I. A. (2012). Human resource management practices in private sector organisations in Pakistan: study of cultural influences. Global Journal of Management and Business Research, 12(7), 20-30. Mirza, M. S., & Rashid, S. (2024). Effect of Online Cooperative Learning on Students’ Academic Achievement at Higher Education Level. Inverge Journal of Social Sciences, 3(2), 1-10. Mumtaz, A., Munir, N., Mumtaz, R., Farooq, M., & Asif, M. (2023). Impact of Psychological & Economic Factors on Investment Decision-Making in Pakistan Stock Exchange. Journal of Positive School Psychology, 130-135. Mushtaque, T., Tunio, M. N., ur Rehman, Z., & Asif, M. (2021). INFLUENCE OF ADMINISTRATIVE EXPERTISE OF HUMAN RESOURCE PRACTITIONERS ON THE JOB PERFORMANCE: MEDIATING ROLE OF ACHIEVEMENT MOTIVATION. International Journal of Management (IJM), 12(4). Nabi, M. K. (2019). The impact of artificial intelligence (AI) on workforce in emerging economies. Global Journal of Management and Business Research, 19(8), 71-78. Nadeem, M., Ali, Y., Rehman, O. U., & Saarinen, L. T. (2024). Barriers and strategies for digitalisation of economy in developing countries: Pakistan, a case in point. Journal of the Knowledge Economy, 15(1), 4730-4749. Nimmagadda, B., Vangaveti, Y., Aaluri, S., Rao, C. M., & Singh, B. (2024). An Analytical study on Navigating Sustainability Challenges and Opportunities in the era of AI and the Gig Economy. In MATEC Web of Conferences (Vol. 392, p. 01044). EDP Sciences. Nishtar, Z., Munir, M. A., Akram, N., Masood, B., Asghar, F., & Meahrayen, M. A. (2023). Green Finance and the Automate Solar Tracking System: Assessing Efficiency, Financial impact, and Environmental Benefits. Inverge Journal of Social Sciences, 2(3), 134-147. Pasha, M. A., Ramzan, M., & Asif, M. (2019). Impact of Economic Value Added Dynamics on Stock Prices Fact or Fallacy: New Evidence from Nested Panel Analysis. Global Social Sciences Review, 4(3), 135-147. Rabbani, W., & Bashir, M. (2022). Deep Dive into Debt Financing and Its Impact on Small Businesses. Journal of Business Insight and Innovation, 1(1), 29–38. Saqlain, M., Anwar, J., & Hameed, B. (2023). A Digital Solution for monitoring the Anxiety Level of University Students. Inverge Journal of Social Sciences, 2(1), 1-16. Saher, N., & Mayrhofer, W. (2014). The role of Vartan Bhanji in implementing HRM practices in Pakistan. The International Journal of Human Resource Management, 25(13), 1881-1903. Shahid, N., Asif, M., & Pasha, A. (2022). Effect of Internet Addiction on School Going Children. Inverge Journal of Social Sciences, 1(1), 13-55. Shaikh, F., Afshan, G., & Sood, K. (2023). Technology and the Change in the Nature of Work. The Impact on HRM Practices: The Protean Career and Boundaryless Career. In The Adoption and Effect of Artificial Intelligence on Human Resources Management, Part B (pp. 31-43). Emerald Publishing Limited. Sumbal, M. S., Tariq, A., Amber, Q., Janovská, K., & Ferraris, A. (2024). Tech revolution unleashed: Navigating the winds of digital transformation in the fast lane. Journal of Innovation & Knowledge, 9(4), 100551. Tanoamchard, W., & Ceienwattanasook, K. (2024). The Future of Work and the Impact of Automation on Jobs in Gig Economy in Thailand: A Review of Literature. Scholar: Human Sciences, 16(1), 77-88. Ungureanu, A. (2019). Industry 4.0. The role of gig economy in the industrial revolution of the 21st century. The USV Annals of Economics and Public Administration, 19(2 (30)), 77-84. Usama, H. A., Riaz, M., Khan, A., Begum, N., Asif, M., & Hamza, M. (2022). PROHIBITION OF ALCOHOL IN QURAN AND BIBLE (A RESEARCH AND ANALYTICAL REVIEW). PalArch's Journal of Archaeology of Egypt/Egyptology, 19(4), 1202-1211.